2024
DOI: 10.3390/vaccines12020216
|View full text |Cite
|
Sign up to set email alerts
|

Co-Administration of Influenza and COVID-19 Vaccines: Policy Review and Vaccination Coverage Trends in the European Union, UK, US, and Canada between 2019 and 2023

Roel C. A. Achterbergh,
Ian McGovern,
Mendel Haag

Abstract: Recommending co-administration of influenza and COVID-19 vaccines has emerged as a strategy to enhance vaccination coverage. This study describes the policy on co-administration and uptake of influenza and COVID-19 vaccination in Europe, the United Kingdom, the United States, and Canada between 2019 and 2023. We collected co-administration policy data from governmental websites, national health organizations, and newspapers. Influenza vaccination coverage among persons ≥65 years and COVID-19 vaccination covera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 30 publications
0
1
0
Order By: Relevance
“…When they calibrated using negative control outcomes, the observed association moved closer to the null and was no longer statistically significant. 13 Following favorable evidence from cohort study and clinical trials [14][15][16] on safety and immunogenicity, co-administration of influenza and COVID-19 vaccines on the same day have been recommended by most public authorities, 17 including the CDC. 5 The safety of coadministration strategy was further studied in a recent VAERS database analysis which concluded that co-administration of bivalent mRNA COVID-19 and seasonal influenza vaccines did not reveal any unusual or unexpected patterns of AEs.…”
Section: Ethics Reviewmentioning
confidence: 99%
“…When they calibrated using negative control outcomes, the observed association moved closer to the null and was no longer statistically significant. 13 Following favorable evidence from cohort study and clinical trials [14][15][16] on safety and immunogenicity, co-administration of influenza and COVID-19 vaccines on the same day have been recommended by most public authorities, 17 including the CDC. 5 The safety of coadministration strategy was further studied in a recent VAERS database analysis which concluded that co-administration of bivalent mRNA COVID-19 and seasonal influenza vaccines did not reveal any unusual or unexpected patterns of AEs.…”
Section: Ethics Reviewmentioning
confidence: 99%
“…Key findings demonstrate a suboptimal vaccination rate among adults, especially those with pre-existing health conditions [ 14 ]. Despite a general trend towards supporting the co-administration of COVID-19 and influenza vaccines, data show significant variability in vaccine coverage across different regions, with Eastern Europe lagging behind Western and Northern Europe and North America [ 15 ]. The studies also highlight the diverse approaches to vaccine recommendations across countries like Germany, Spain, the UK, and Italy, ranging from strict evidence-based criteria to more flexible real-world evidence considerations [ 16 ].…”
Section: Introductionmentioning
confidence: 99%